Islamic inscriptions - Blair, Sheila (Edinburgh University Press, 1998)
The first object created by God, according to early Muslim commentators, was the pen, which he used to chronicle events to come. The word, in its various manifestations, is central to the Islamic faith. Surely a reflection of this centrality, profuse inscriptions mark countless Islamic objects, from the humblest oil lamps and unglazed ceramics to the finest and most expensive rock crystals and jades. The inscriptions serve numerous functions: decorating, proclaiming ownership and patronage, proffering good wishes and proverbs, and spreading religious texts throughout the world. Aside from their aesthetic worth, these inscriptions provide a fascinating window onto a distant culture. In Islamic Inscriptions, Sheila S. Blair a wealth of stunning images and incisive commentary, while also providing the newcomer to Islamic civilization with a key to unlocking the mysteries of Islamic epigraphy. In addition to chapters devoted to the main types of inscription, detailing the development of their content and style, inscriptive techniques, and the motivations behind them, the book provides practical knowledge on finding, identifying, interpreting, researching, and recording inscriptions. The variety and clarity of information presented makes Islamic Inscriptions an ideal reference for historians, curators, archaeologists, and collectors.